AI and business rule engines for Excel power users capture and scale your business knowledge into the cloud - with Microsoft Office 365, decision models, and AI tools from IBM and Red Hat - Browne, Paul (PACKT PUBLISHING LIMITED, 2023)
A power-packed manual to enhance your decision-making with the application of Business Rules using KIE, Drools, Kogito, MS Excel, Power Automate, Office Script, and MS Forms Purchase of the print or Kindle book includes a free PDF eBook Key Features Explore the business rule tools by implementing real-world examples to write sophisticated rules Discover how decision services solve current business challenges using AI Combine rules with workflows and scripting to deploy a cloud-based production environment Book Description Microsoft Excel is widely adopted across diverse industries, but Excel Power Users often encounter limitations such as complex formulas, obscure business knowledge, and errors from using outdated sheets. They need a better enterprise-level solution, and this book introduces Business rules combined with the power of AI to tackle the limitations of Excel. This guide will give you a roadmap to link KIE (an industry-standard open-source application) to Microsoft's business process automation tools, such as Power Automate, Power Query, Office Script, Forms, VBA, Script Lab, and GitHub. You'll dive into the graphical Decision Modeling standard including decision tables, FEEL expressions, and advanced business rule editing and testing. By the end of the book, you'll be able to share your business knowledge as graphical models, deploy and execute these models in the cloud (with Azure and OpenShift), link them back to Excel, and then execute them as an end-to-end solution removing human intervention. You'll be equipped to solve your Excel queries and start using the next generation of Microsoft Office tools. What you will learn Use KIE and Drools decision services to write AI-based business rules Link Business Rules to Excel using Power Query, Script Lab, Office Script, and VBA Build an end-to-end workflow with Microsoft Power Automate and Forms while integrating it with Excel and Kogito Collaborate on and deploy your decision models using OpenShift, Azure, and GitHub Discover advanced editing using the graphical Decision Model Notation (DMN) and testing tools Use Kogito to combine AI solutions with Excel Who this book is for This book is for Excel power users, business users, and business analysts looking for a tool to capture their knowledge and deploy it as part of enterprise-grade systems. Working proficiency with MS Excel is required. Basic knowledge of web technologies and scripting would be an added advantage.